Knowledge Management; Suatu Strategi Membentuk Sistem Penjaminan Mutu Internal Perguruan Tinggi Swasta - Sipahelut, Semuel Willem; Ubjaan, Jusak (Lembaga Penelitian & Pengabdian Masyarakat (LPPM) STIA Said Perintah, 2023)
Acceptance of the output of higher education in the world of work with various quality standards that are always increasing is the main prerequisite, demanding tertiary institutions, including private universities, to improve their internal quality assurance system so as to produce better accreditation of study programs and study programs. institution. To answer these demands, private tertiary institutions must develop various organizational strategies that can contribute to improving the quality of higher education. Knowledge Management is a strategy that can be used to improve the quality of education. Technically improving the quality of tertiary institutions can be done by following the steps of the knowledge management system. That is starting from capturing, sharing, applying, and finding knowledge about the internal higher education quality assurance system that meets and exceeds national higher education standards. So it is hoped that a quality culture that will facilitate tertiary institutions to gain public trust through better accreditation values is expected to develop.